Talent management for civil service in Ukraine: organizational and management mechanisms of development - Rachynskyi, Anatolii (Theory and Practice of Public Administration, 2026)
The article explores the theoretical foundations, current state, and prospects for developing talent management in the Civil Service of Ukraine. The relevance of the study is driven by the need to strengthen the institutional capacity of public authorities amid full-scale war, workforce shortages, digital transformation, European integration reforms, and post-war recovery. The study demonstrates that the traditional personnel management model, primarily focused on administrative procedures and regulatory compliance, no longer meets the strategic development needs of the public sector. Based on the analysis of contemporary scholarly approaches, the concept of talent management in the civil service context is refined, and its role within strategic human resource management is identified. The study substantiates the feasibility of combining inclusive and selective approaches to talent development, considering the specific characteristics of public administration, as well as the principles of professionalism, integrity, political impartiality, and commitment to the public interest. A comprehensive assessment of the current state of the talent management system in the Civil Service of Ukraine was conducted through the analysis of the national regulatory framework, official statistics, materials of the National Agency of Ukraine on Civil Service, OECD reports, and SIGMA Programme documents. The findings indicate that, despite the establishment of regulatory, organizational, and digital prerequisites for HR function development, strategic workforce planning, employee potential assessment, professional development, succession management, career mobility, and digital HR analytics remain insufficiently integrated. The key challenges identified include the reactive approach to workforce planning, the predominance of administrative personnel functions, the limited use of HR analytics, the absence of systematic succession management, and the lack of personalized professional development pathways. The scientific novelty of the study lies in the development of an organizational and managerial framework for the advancement of the talent management system in the Civil Service of Ukraine. The proposed mechanism integrates strategic workforce planning, comprehensive performance and employee potential assessments, personalized development pathways, internal mobility, talent pools, succession management, employee retention mechanisms, and digital HR analytics into an integrated continuous talent management cycle. The implementation of the proposed mechanism will contribute to strengthening civil service workforce resilience, improving human capital utilization, fostering public sector leadership, and enhancing the capacity of public administration to achieve Ukraine’s long-term strategic development priorities.